2008
DOI: 10.1152/ajpregu.90478.2008
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction optimizes the proteasome pathway with aging in rat plantaris muscle: implications for sarcopenia

Abstract: Hepple RT, Qin M, Nakamoto H, Goto S. Caloric restriction optimizes the proteasome pathway with aging in rat plantaris muscle: implications for sarcopenia. Am J Physiol Regul Integr Comp Physiol 295: R1231-R1237, 2008. First published August 13, 2008 doi:10.1152/ajpregu.90478.2008.-To gain insight into the significance of alterations in the proteasome pathway for sarcopenia and its attenuation by calorie restriction, we examined protein oxidation and components of the proteasome pathway in plantaris muscle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
47
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 52 publications
7
47
2
Order By: Relevance
“…These data were consistent with the results of many other studies have demonstrated that insulin-mediated glucose uptake by skeletal muscle is also greater for CR compared with AL rats (8,17,42,56). The results with isolated muscles are also consistent with the results of previous studies that have measured whole body insulin sensitivity in adult CR versus AL rats by various methods, including glucose infusion rate during a euglycemichyperinsulinemic clamp (23,33).…”
Section: R132 Calorie Restriction and Mapk Signaling In Skeletal Musclesupporting
confidence: 91%
“…These data were consistent with the results of many other studies have demonstrated that insulin-mediated glucose uptake by skeletal muscle is also greater for CR compared with AL rats (8,17,42,56). The results with isolated muscles are also consistent with the results of previous studies that have measured whole body insulin sensitivity in adult CR versus AL rats by various methods, including glucose infusion rate during a euglycemichyperinsulinemic clamp (23,33).…”
Section: R132 Calorie Restriction and Mapk Signaling In Skeletal Musclesupporting
confidence: 91%
“…4 and 5). Elevated 20S proteasome levels were previously reported in muscles from aged F344/BN and LOU rats (17)(18)(19)55), but Ferrington and co-workers (18,55) found the expression of the 19S (PA700) unchanged. However, in those studies proteasomes were measured after ultracentrifugation in a buffer lacking ATP, which is necessary to maintain the structural integrity of the 26S.…”
Section: Discussionmentioning
confidence: 82%
“…19 In the muscle, variable results have been reported, depending on the muscle, age and model (rat, monkey). 42 --44 Hepple et al 42 showed that proteosome activity in muscle during caloric restriction decreased in line with muscle mass, but Chambon --Savanovitch et al 45 did not report any effect of energy restriction on 3-metylhistidine excretion in old rats. During our study, energy restriction did not cause any loss of muscle mass, and the lack of any effect on the mRNA-encoding key enzymes involved in proteolysis pathways (at least the proteasome pathway) was consistent with the observations made by Hepple et al 42 By contrast, we determined a marked effect of the protein level on the muscle gene expression of these enzymes, whatever the pathway.…”
mentioning
confidence: 99%
“…42 --44 Hepple et al 42 showed that proteosome activity in muscle during caloric restriction decreased in line with muscle mass, but Chambon --Savanovitch et al 45 did not report any effect of energy restriction on 3-metylhistidine excretion in old rats. During our study, energy restriction did not cause any loss of muscle mass, and the lack of any effect on the mRNA-encoding key enzymes involved in proteolysis pathways (at least the proteasome pathway) was consistent with the observations made by Hepple et al 42 By contrast, we determined a marked effect of the protein level on the muscle gene expression of these enzymes, whatever the pathway. This could be explained by the fact that protein consumption in the HP-R group was nearly 3-fold that of the OI-R group, and 2-fold that of the OI rats, and was in line with the down-regulation of proteolysis pathways by amino acids in muscle.…”
mentioning
confidence: 99%